A physiologically based approach to prescribing exercise following a sport-related concussion - Worts, P. R.; Burkhart, S. O.; Kim, J.-S. (Sports Medicine, 2019)
Clinical management of concussion has evolved over the last 20 years, and complete cognitive and physical rest remains a common clinical recommendation. The duration of rest may vary widely, from 24-48 h to several weeks or until the patient`s symptoms have resolved or returned to near baseline levels. Following a period of rest, a stepwise progression of exercise is used for gradual return to play or to work. Previous research in healthy people suggested that prolonged periods of physical inactivity consistently induced deleterious physiological and psychological effects. A growing body of evidence indicates that initiating exercise earlier in the recovery process following a concussion may reduce symptom burden and lower the incidence of post-concussion syndrome. Preliminary findings appear promising, but data on the appropriate exercise prescription for patients who recently sustained a concussion are limited. We reviewed the literature in healthy individuals and patients with concussion and post-concussion syndrome to develop a physiologically based exercise prescription for the days following a concussion. Using this, practitioners may shorten the rest period and initiate controlled exercise earlier during the recovery process following a concussion.